PENGARUH KOMPETENSI KEPRIBADIAN GURU PAI TERHADAP KECERDASAN EMOSIONAL SISWA DI SMP NEGERI 06 PALEMBANG - Lestari Arisca; Karoma Karoma; Ahmad Syarifuddin; Syarnubi Syarnubi (PAI RAFAH, 2020)
The problem in this study is knowing how the teacher teaches in the teaching and learning process by looking at the teacher's personality and the student's condition during the teaching and learning process, in the learning process students sometimes cannot respond to good teacher behavior, so there are still many students who behave less well, the low emotional intelligence of students and teachers has not been maximal in giving a good influence on students. The purpose of this study was to determine the effect of PAI teacher personality competence on the emotional intelligence of students at SMP Negeri 06 Palembang.This research uses a descriptive quantitative method while the type of approach used in this research is correlational, that is, to find the relationship between the two variables. While the data collection technique is by distributing questionnaires. The questionnaire was distributed to students and the answers were calculated using the percentage formula then processed and explained descriptively, and calculating the two variables using the product-moment formula.Based on the research results, it is known that the product-moment correlation value is that the teacher's personality competence is high with a percentage of 35 (65%) while the emotional intelligence of students is high with a percentage of 30 (60%) in the significance calculation obtained at r count =. 0.243 In the table r table 5% = 0.254 and 1% =. 0.330 with this then Ha is accepted and Ho is rejected so that it is concluded that there is an influence of PAI teacher's personality competence on the emotional intelligence of students at SMP Negeri 06 Palembang. Therefore, Ha is accepted and Ho is rejected, so the hypothesis that says there is an influence of PAI teacher's personality competence on the emotional intelligence of students at SMP Negeri 06 Palembang.